1998
DOI: 10.1021/tx980022n
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Heterocyclic Aromatic Amines by Rat and Human Liver Microsomes and by Purified Rat and Human Cytochrome P450 1A2

Abstract: The dietary mutagens 2-amino-3,8-dimethylimidazo[4,5-f]quinoxaline (MeIQx) and 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP) are activated to genotoxins by rat and human liver cytochrome P450 (P450) 1A1- and 1A2-mediated N-oxidation. Immunoquantitation of 51 human liver samples revealed a wide range in P450 1A2 expression (10-250 pmol/mg of microsomal protein, median 71 pmol/mg), with 39% of the livers containing >100 pmol/mg of protein. There was no evidence for expression of P450 1A1 (<1 pmol/mg of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
231
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(246 citation statements)
references
References 45 publications
14
231
0
Order By: Relevance
“…IQ has been shown to be metabolized by human CYP1A1 and 1A2, although to a much greater extent by CYP1A2 (McManus et al, 1990). However, of relevance to these studies, BNF increases CYP1A1 activity to a greater degree than 1A2 activity in rodents (Turesky et al, 1998). Preliminary studies with liver slices from young rats have demonstrated almost complete blockage of 5-O-glucuronide and 5-sulfate formation by ellipticine, a CYP1A1 inhibitor (data not shown).…”
Section: Discussionmentioning
confidence: 92%
“…IQ has been shown to be metabolized by human CYP1A1 and 1A2, although to a much greater extent by CYP1A2 (McManus et al, 1990). However, of relevance to these studies, BNF increases CYP1A1 activity to a greater degree than 1A2 activity in rodents (Turesky et al, 1998). Preliminary studies with liver slices from young rats have demonstrated almost complete blockage of 5-O-glucuronide and 5-sulfate formation by ellipticine, a CYP1A1 inhibitor (data not shown).…”
Section: Discussionmentioning
confidence: 92%
“…17,18) Levels of CYP1A2 protein induced by MeIQx were significantly decreased to almost normal levels by the concomitant administration of 2% bLF at weeks 3 and 8 in the liver, independently of initial DEN treatment (Fig. 3).…”
Section: Discussionmentioning
confidence: 95%
“…PhIP undergoes N-hydroxylation by cytochromes P4501A1 and P4501A2 at the two-amino position [42] to generate the mutagenic metabolite [43]. Since P4501A1 is not expressed abundantly in liver [44] and P4501A2 is limited to expression in hepatic tissue, it has been proposed [45] that N-hydroxy-PhIP is transported from the liver in the circulation to target tissues where it forms DNA adducts. Thus, understanding which of the UGTs participates in the metabolism of PhIP is important.…”
Section: Discussionmentioning
confidence: 99%